Nicotine addiction and overweight affect intrinsic neural activity and neurotransmitter activity: A fMRI study of interaction effects. Issue 3 (22nd December 2022) - Gao, Xinyu; Zhang, Mengzhe; Yang, Zhengui; Niu, Xiaoyu; Zhou, Bingqian; Chen, Jingli; Wang, Weijian; Wei, Yarui; Han, Shaoqiang; Cheng, Jingliang; Zhang, Yong
Abstract : Background: Nicotine addiction and overweight often co‐exist, but the neurobiological mechanism of their co‐morbidity remains to be clarified. In this study, we explore how nicotine addiction and overweight affect intrinsic neural activity and neurotransmitter activity. Methods: This study included 54 overweight people and 54 age‐, sex‐, and handedness‐matched normal‐weight individuals, who were further divided into four groups based on nicotine addiction. We used a two‐way factorial design to compare intrinsic neural activity (calculated by the fALFF method) in four groups based on resting‐state functional magnetic resonance images (rs‐fMRI). Furthermore, the correlation between fALFF values and PET‐ and SPECT‐derived maps to examine specific neurotransmitter system changes underlying nicotine addiction and overweight. Results: Nicotine addiction and overweight affect intrinsic neural activity by themselves. In combination, they showed antagonistic effects in the interactive brain regions (left insula and right precuneus). Cross‐modal correlations displayed that intrinsic neural activity changes in the interactive brain regions were related to the noradrenaline system (NAT). Conclusion: Due to the existence of interaction, nicotine partially restored the changes of spontaneous activity in the interactive brain regions of overweight people. Therefore, when studying one factor alone, the other should be used as a control variable. Besides, this work links the noradrenaline system with intrinsic neural activity in overweight nicotine addicts. By examining the interactions between nicotine addiction and overweight from neuroimaging and molecular perspectives, this study provides some ideas for the treatment of both co‐morbidities.